Penggunaan strategi berfikir kreatif dalam kalangan pelajar sekolah menengah atas (SMA) - Abang Ishar, Abang Yaman (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The objective of this study is to explore the thinking potentials of students to the optimun. To achieve this objective, the student's studying techniques is associated with the use of creative strategy and the various methods of studying. There are 23 respondents chosen as the study sampling. The research method for this study is the qualitative method based on descriptive approach. Data collection is by means of observation and interviews. Data analysis is based on qualitative data analysis using content analysis. The finding show that out of 23 respondents chosen through purposive sampling, 21 of them reveals that they were using the creative strategy and the various study methods to achieve outstanding result in their National Examination (in the case of Malaysia is Sijil Tinggi Pelajaran Malaysia).